2021
DOI: 10.1097/gco.0000000000000717
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections in gynecology: the latest evidence for prevention and management

Abstract: Purpose of review Surgical site infection (SSI) remains one of the most common postoperative surgical complications. Prevention and appropriate treatment remain paramount. Recent findings Evidence-based recommendations include recognition and reduction of preoperative risks including hyperglycemia and smoking, treatment of preexisting infections, skin preparation with chlorhexidine gluconate, proper use of preoperative antibiotics, and implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…However, despite these multifaceted benefits, postoperative infections after laparoscopic radical nephrectomy can impair the recovery process and increase hospitalization costs. Although the associated risks are relatively low, infection remains a concern, emphasizing the necessity of strict surgical protocols and meticulous postoperative management 17,18 . This type of infection may exist in various forms, from local wound infections to urinary tract infections and even systemic sepsis; this depends on the characteristics and scope of bacterial infiltration 19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite these multifaceted benefits, postoperative infections after laparoscopic radical nephrectomy can impair the recovery process and increase hospitalization costs. Although the associated risks are relatively low, infection remains a concern, emphasizing the necessity of strict surgical protocols and meticulous postoperative management 17,18 . This type of infection may exist in various forms, from local wound infections to urinary tract infections and even systemic sepsis; this depends on the characteristics and scope of bacterial infiltration 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the associated risks are relatively low, infection remains a concern, emphasizing the necessity of strict surgical protocols and meticulous postoperative management. 17,18 This type of infection may exist in various recuperation time and inflate cumulative medical expenses. In addition, relevant studies have shown that infection is a prevalent complication during the treatment of patients with this disease, and complications have a significant impact on their postoperative survival.…”
Section: Discussionmentioning
confidence: 99%
“…ISSI includes incisional and space infections, which can be decreased through serial measures such as having the patient shower or bath before surgery, disinfecting the skin in the operating room before surgery, administering prophylactic antibiotics when properly indicated, ensuring medical optimization of the patient, and ensuring a particle-free operating environment. [17][18][19][20] Skin preparation is not recommended to be performed before conventional laparoscopic surgery or laparotomy. 21,22 Current skin disinfection methods fail to eliminate all organisms on the epidermis and do not penetrate below the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 While laparoscopic techniques offer many advantages over traditional open surgeries, they come with unique challenges and risks, especially concerning SSIs. 20 Given the intricacies and specialized nature of the procedure, understanding the risk factors specific to SSIs in laparoscopic radical nephrectomy for RCC becomes paramount. 21 This study's focus on laparoscopic radical nephrectomy for RCC is essential as it addresses a significant gap in the literature, where generalized findings from broader urological surgeries might not fully apply.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of renal cell carcinoma (RCC) has been on the rise, and laparoscopic radical nephrectomy has emerged as a leading surgical intervention for the condition 18,19 . While laparoscopic techniques offer many advantages over traditional open surgeries, they come with unique challenges and risks, especially concerning SSIs 20 . Given the intricacies and specialized nature of the procedure, understanding the risk factors specific to SSIs in laparoscopic radical nephrectomy for RCC becomes paramount 21 .…”
Section: Introductionmentioning
confidence: 99%